C.451dupT in KLKB1 is common in Nigerians, confirming a higher prevalence of severe prekallikrein deficiency in Africans compared to Europeans. (18th November 2020) - Adenaeuer, Anke; Ezigbo, Eyiuche D.; Fawzy Nazir, Hanan; Barco, Stefano; Trinchero, Alice; Laubert‐Reh, Dagmar; Strauch, Konstantin; Wild, Philipp S.; Lackner, Karl J.; Lämmle, Bernhard; Rossmann, Heidi
Abstract : Essentials Prekallikrein (PK) deficiency is a recessive trait with isolated aPTT prolongation. KLKB1 c.451dupT is common in Nigerians (7/600 alleles) and absent in a European group (0/600). To date, all genotyped PK‐deficient patients of African ancestry were homozygous for 451dupT. Diagnostics of isolated aPTT prolongation in African descendants should include PK testing. Abstract: Background: Severe prekallikrein deficiency (PK deficiency) is an autosomal‐recessive condition thought to be very rare. Recently we reported that the previously unnoticed variant c.451dupT, p.Ser151Phefs*34 in KLKB1, which is listed in databases aggregating genome data, causes PK deficiency and is common in Africans according to gnomAD (allele frequency 1.43%). Patients/Methods: The most common African (c.451dupT) and European (c.1643G>A, p.Cys548Tyr) PK deficiency causing KLKB1 variants were analyzed in two population‐based collectives of 300 Nigerian and 300 German subjects. Genome databases were evaluated for variant frequencies and ethnicity of the subjects. The geographic origin of PK‐deficient cases due to 451dupT was assessed. Results: Two of five patients with PK deficiency caused by homozygous 451dupT were African, one African American, one from Oman, and one of unknown origin. The frequency of 451dupT was 1.17% in the Nigerian collective (7/600 alleles); none had Cys548Tyr. Subjects with 451dupT were found among different Nigerian ethnicities. Both variants were absent in the European collective. Database research was compatible with these findings, even though mainly data of African Americans (451dupT: 1.12%‐1.78%) was accessible. A relevant number of non‐American Africans are included only in the 1000Genomes collective: 451dupT frequency was 1.29% in native Africans and 1.56% in African Caribbeans. Conclusions: This study underlines the higher prevalence of PK deficiency among people with African descent compared to Europeans. In order to avoid delay of necessary surgical procedures in patients of African origin, diagnostic algorithms for isolated, unexplained, activated partial thromboplastin time prolongation in these subjects should include PK deficiency screening.